PERTUMBUHAN KACANG HIAS (Arachis pintoi) PADA MEDIA TANAH PASCA PENAMBANGAN BATUBARA YANG DIPERKAYA MIKORIZA, KAPUR DAN PUPUK NPK - Willie Samodra Laya; Moehansyah Moehansyah; Jamzuri Hadie (Universitas Lambung Mangkurat, 2016)
This study aimed to determine the effects of the provision of arbuscular mycorrhizal fungi (AMF), the provision of lime, and the provision of NPK fertilizer, and the interaction effect of the provision of Arbuscular mycorrhizal fungi (AMF), lime and NPK fertilizers in promoting the growth of pinto peanut in the soil media of post-mining land. The research method used was a completely randomized design (CRD) three-factor factorial with the first factor is the type of inoculant FMA (M) = 3 levels, the second factor is the provision of lime (K) = 3 levels, and the third factor is the NPK fertilizer (P) = 3 levels. These results indicated that the interaction between AMF Glomus sp. and NPK fertilizer dose of 1 gram/polybag can increase height increase pinto peanut plants for 34.16 % of the controls. The interaction between AMF Gigaspora sp. The lime dose of 50 % Al-dd and Fertilizers NPK dose of 1 gram/polybag can increase the growth of leaves pinto peanut plants at 108.33 % of the controls. The interaction between AMF Glomus sp. and NPK fertilizer dose of 2 grams/polybag can increase canopy and root biomass pinto peanut plants at 245.21 % of the controls. The interaction between AMF Glomus sp. and NPK fertilizer dose of 2 grams/polybag can increase canopy and root biomass pinto peanut plants at 245.21 % of the controls. Level relative mycorrhizal dependency (RMD) was influenced by the type of AMF plant inoculated host. Highest RMD shown in pinto peanut using AMF Glomus sp. is 31.99% at moderately dependent.